The Relationship of Professional Ethics with Social Competence and Job Performance Case Study: Staff of Zahedan Technical and Vocational Training Organization - Farzaneh Shaghozaei; Afsaneh Marziyeh; Naser Nastezaei (پژوهش‌های مدیریت عمومی, 2018)
Abstract One of the basic variables affecting organizational behavior is job performance. This study was conducted to determine the relationship of professional ethics with social competence and job performance. Research method of the current study was descriptive-correlational and using a stratified random sampling method, among all staff of Zahedan Technical and Vocational Training Organization in 2016, a corpus of 123 people was studied by applying three questionnaires on professional ethics (Gregory, 1990), social competence (Fellner, 1990), and job performance (Paterson, 1970). To analyze the data, a Pearson correlation coefficient and a multiple regression analysis were used via SPSS21. Results showed that professional ethics and its components, including attachment to and interest in work, perseverance and seriousness in work, healthy human relationships at work, and collective spirit and participation in work, were significantly and directly related to social competence (P<0.01). Moreover, results of the regression analysis indicated that professional ethics was able to determine 39.3% of variances in social competence and among all the components of professional ethics, perseverance and seriousness in work and collective spirit and participation in work had the highest predictive powers (P<0.05). Other results demonstrated that professional ethics and its components, i.e. attachment to and interest in work, perseverance and seriousness in work, healthy human relationships at work, and collective spirit and participation in work, were significantly and directly related to job performance (P<0.01).  In addition, results of the regression analysis indicated that professional ethics was able to determine 38.1% of variances in job performance and among all the components of professional ethics, perseverance and seriousness in work and attachment to and interest in work had the highest predictive powers (P<0.05). Given these results, it can be concluded that the more the levels of staff’s professional ethics, the more their social competence and job performance.  Introduction Organizations are social institutions which, like other types of institutions, include people whose main job is to handle the responsibility of administering these institutions. Job performance is one of the components affecting an organization which has played an important role in studies conducted on various organizations and has been the main focus of such studies (Andam, Montazeri, & Abavisani, 2015). Job performance, as an expected overall value of an organization, is regarded as an indicator for determining levels of efficiency and productivity in the organization. There are different viewpoints on job performance. Job performance refers to a degree to which staff carry out jobs assigned to them in a given working condition and, as general values expected by an organization, it is defined based on distinct pieces of behaviors which are done by a person over a given period of time (Motowidlo, 2003, as cited in Hassani, 2015).  Studies have indicated that people’s job performance is influenced by motivations, abilities, characteristics, clarity of roles, and having an opportunity of doing activities and the ability of human resources itself is dependent on occupational knowledge and skills needed to perform occupational tasks and activities (Robbins, 1997).  Another component that can affect individual and organizational effectiveness is social competence. Social competence is a complex variable linked to an individual's ability to manage emotions and is a combination of motivational drives, cognitive abilities, social competence, and behavioral skills (Cunningham, 2009, as cited in Shariatmadar & Pourgravand, 2014). Green and Rechis (2006) argued that to strengthen social competence, levels of cooperation, responsiveness and effectiveness, acceptance of social responsibilities, behaving in a friendly way, and other positive interaction practices should be improved among students. Cheung and Lee (2010) laid an emphasis on school teaching practices, interpersonal interactions, and interactions with a teacher as sources supporting or complementing parental behaviors; since they create opportunities for learning and practicing social competence. Among the most important issues that have caused many problems for organizations around the world, problems caused by corruption and misconduct can be mentioned (Arshadi & Piriaei, 2014). While in the Western world and in the field of organization and management, there is a branch known as professional ethics, in our organizational and managerial society, little attention has been paid to professional ethics (Jafariani & Yazarlou, 2015). Several definitions have been proposed for professional ethics. As an example, professional ethics refers to ethical issues and questions, considers ethical principles and values ​ in a professional system, and administers professional ethics in a professional environment (Maarefi, Ashk Torab, Abaszadeh, Alavi Majd, & Eslami Akbar, 2014).  Professional ethics is one of the new branches of ethics that seeks to answer various ethical issues and attempts to consider certain principles for them (Mortazavi, Irannejad Parizi, & Jafari, 2014). Failure to adhere to some ethical standards has raised many concerns in governmental and non-governmental sectors (Ahmadi, Safari Kahreh, Mirmahdi, & Esmaili Kakhaki, 2013). In our society, despite many positive elements in our national and religious culture according to which a great value is given to work, a number of values dominate the general structure of the society ​​that undermines work ethics as well as work conscience (Ghajari & Heidari, 2015). One of the most important educational organizations which can play a key role in training human resources needed by communities and have been considered by different countries all over the world due to the ever-increasing changes taken place in the field of knowledge and technology is the technical and vocational training organization. According to the mentioned issues and due to the fact that, as far as the authors checked, no similar studies have been conducted to examine the issue, the main objective of carrying out this study was to determine the relationship of professional ethics with social competence and job performance among staff of Zahedan Technical and Vocational Training Organization. Case Study The current study had a statistical population including all staff of Zahedan Technical and Vocational Training Organization in 2016 who were 181 people. Based on the Cochran’s sampling formula, 123 people, 54 women (43.9%) and 69 men (56.1%), were selected based on their gender using the stratified random sampling method. Materials and Methods The research method of the present study was descriptive-correlational. Measurement tools used in the current study were questionnaires. To measure professional ethics, social competence, and job performance among the staff, questionnaires on professional ethics (Gregory, 1990), social competence (Fellner, 1990), and job performance (Paterson, 1970) were respectively used. The validity and reliability of all these three questionnaires were also examined. Results and Discussion The first finding obtained from this study showed that the statuses of professional ethics, social competence, and job performance among the staff were higher than the average. This finding is consistent with results of a number of previously carried out studies (Shahinmehr & Hasani, 2015; Soleimani, Abbaszadeh, & Azizi, 2012).  The second finding of this study indicated that professional ethics and its components (attachment to and interest in work, perseverance and seriousness in work, healthy human relationships at work, and collective spirit and participation in work) were significantly and directly related to the staff’s social competence. The results of the regression analysis demonstrated that professional ethics could determine 39.3% of the variances in social competence. The results obtained from examining the relationship of professional ethics and its components with job performance among the staff of Zahedan Technical and Vocational Training Organization demonstrated that professional ethics and its components were significantly and directly related to job performance. Based on the regression model, professional ethics could determine 38.1% of the variances in job performance. Conclusion In the present era, when analyzing behaviors of various organizations, addressing ethics and paying attention to ethical values are among the requirements. Ethical behaviors constitute the external symbols of organizations which themselves are the sum of a variety of ethical values in which organizations emerged and evolved. In the current situation, failure to adhere to some ethical standards has raised many concerns in governmental and non-governmental sectors. Therefore, considering the findings of this study regarding the positive and significant relationships of the components of professional ethics with social competence and job performance, managers of different organizations are highly recommended to hold various workshops to train the components of professional ethics, including perseverance and seriousness in work and attachment to and interest in work, and methods of observing the principles of human relations in work to their staff to provide the grounds for promoting their social competence and improve their job performance.